THE INFLUENCE OF LEADERSHIP STYLE AND MOTIVATION ON TEACHER PERFORMANCE TO STUDENTS TO IMPROVE THE QUALITY OF MIDDLE SCHOOL LEARNING IN JIRAK JAYA DISTRICT - Indah Kristian; Nur Ahyani; Mahasir Mahasir (Esteem Journal of English Education Study Programme, 2023)
Educational efforts are planned to influence other people, both individuals, groups, and communities so that they do what is expected by educators. This study provides a problem definition for the object of the research problem on the Influence of Leadership Style and Motivation on Teacher Performance in Junior High Schools Jirak Jaya District Musi Banyuasin Regency. The method in this research is a quantitative method with a survey approach using the Cluster Random Sampling Area technique and data analyzed using the SPSS Software For Windows Version 21 assistance program. The result in this research there are significant influence of leadership style on the performance of Junior High School teachers in Jirak Jaya District and contributes 29.7%, the performance of Junior High School teachers based on effect of teacher work motivation in Jirak Jaya District and contributes 29.4% of the influence, and the performance of Junior High School teachers based on leadership style and work motivation in Jirak Jaya District and contributes 70.8% influence, and the rest is influenced by other factors not listed in this study.